Incremental Predictive Value of Plasma Renin Activity as a Prognostic Biomarker in Patients with Heart Failure - Park, Bo Eun; Yang, Dong Heon; Kim, Hyeon Jeong; Park, Yoon Jung; Kim, Hong Nyun; Jang, Se Yong; Bae, Myung Hwan; Lee, Jang Hoon; Park, Hun Sik; Cho, Yongkeun; Chae, Shung Chull (Journal of Korean medical science, 2020)
The association of N-terminal pro-B type natriuretic peptide (NT-proBNP) and plasma renin activity (PRA) for the prognosis of the patients with acute heart failure (HF) has not been fully investigated. This study aimed to determine the association between NT-proBNP and PRA and to investigate the incremental value of PRA to NT-proBNP for predicting long term prognosis in patients with acute HF. Three hundred and ninety-six patients (mean age, 64.7 ± 15.9 years; 46.5% female) presenting with acute HF were enrolled between December 2004 and July 2013. Patients with newly diagnosed HF as well as patients with acute exacerbated chronic HF were included. The prognosis was assessed with the composite event of all-cause mortality and readmission for HF during a 2-year follow-up period. The etiology of HF was ischemic in 116 (29.3%) patients. In a Cox proportional hazards model, log-transformed PRA (hazard ratio [HR], 1.205; = 0.007) was an independent predictor of the composite outcome of all-cause mortality and readmission for HF in addition to age (HR, 1.032; = 0.001), white blood cell (WBC) count (HR, 1.103; < 0.001), and left ventricular ejection fraction (LVEF) (HR, 0.978; = 0.013). Adding PRA to age, sex, LVEF, and NT-proBNP significantly improved the prediction for the composite outcome of all-cause mortality and readmission for HF, as shown by the net reclassification improvement (0.47; < 0.001) and integrated discrimination improvement (0.10; < 0.001). PRA could provide incremental predictive value to NT-proBNP for predicting long term prognosis in patients with acute HF.